2006
DOI: 10.1292/jvms.68.235
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Characteristics of Ito Cells and Kupffer Cells in the Feline Liver

Abstract: ABSTRACT. The histopathological characteristics of Ito cells and Kupffer cells were investigated in the liver of 21 cats (age range: 6 months -18 years) autopsied in our laboratory during 2003. Immunohistochemical examinations were performed using antibodies against lysozyme, desmin and α-smooth muscle actin. No Kupffer cells reacted with the antibody against lysozyme. However, macrophages in the lung and spleen showed a positive reaction with the antibody. This finding suggests a possibility that the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
(19 reference statements)
0
11
2
Order By: Relevance
“…In the feline liver, large vacuole-laden Ito cells are observed only in adults, and not in young cats under 2 years old [17]; however, in this study, Ito cells in the porcine and bovine liver did not show such age-dependent changes. It is necessary to examine aged porcine and bovine livers to elucidate age-dependent changes.…”
contrasting
confidence: 89%
See 2 more Smart Citations
“…In the feline liver, large vacuole-laden Ito cells are observed only in adults, and not in young cats under 2 years old [17]; however, in this study, Ito cells in the porcine and bovine liver did not show such age-dependent changes. It is necessary to examine aged porcine and bovine livers to elucidate age-dependent changes.…”
contrasting
confidence: 89%
“…As ECMs in hepatic fibrosis are produced by activated Ito cells, there may be some functional relationship between vitamin A accumulation and Ito cell activation. Although no positive reaction for α-SMA, a marker of activated Ito cells, was observed in porcine and bovine Ito cells in this study, some large vacuole-laden feline Ito cells were shown to be positive for α-SMA [17]; therefore, the amount of lipid in Ito cells may influence the morphology and function. In conclusion, the histopathological characteristics of Kupffer cells and Ito cells in porcine and bovine liver differed from those of felines in terms of immunohistochemical features and lipid content.…”
contrasting
confidence: 80%
See 1 more Smart Citation
“…The mammalian liver is a morphologically and functionally complex organ, made up not only of the largely predominant parenchymal cells (hepatocytes), but also non-parenchymal cells (N-PCs), including Ito, Kupffer and sinusoidal endothelial cells (SECs), as well as other cell types that reside in the sinusoidal compartment [1][2][3]. Although present in a small percentage in the total liver volume (around 6%), non-parenchymal cells play an important role in the regulation of many hepatocyte functions [1,4] as well as in the immunobiology of the liver [5], in both normal and pathological conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…21 Lysozyme is a conserved proteolytic enzyme expressed in many leukocytes of myelomonocytic lineage in mammals. 22 Antibodies to proliferating cell nuclear antigen (PCNA) and p53 were used to evaluate the replicative cycle of the infected cells. PCNA is a subunit of DNA polymerase d and it is mainly expressed during the S phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%